The role of the nonprofit economic companies in human resource management in Hungary - Orbán, Szabolcs Gergely (International Journal of Engineering and Management Sciences, 2019)
In the changed labor market structure in the context of economic growth in Hungary, the reintegration of displaced and increasingly differentiated groups into the world of work has become an indispensable necessity, with alternative initiatives aimed at long-term profit maximization. Nonprofit economic companies replacing former public benefit companies not only determine the revenues of the whole nonprofit sector in their operations, their work goes beyond this, as most of them are engaged in socially marginalized, disadvantaged, or even disabled people, and can do other work to improve employability and employment. The aim of my study was to process the latest statistical database of the nonprofit sector issued by the KSH in order to determine the role of nonprofit economic companies in employment, by appying secondary analysis.